A visibilidade das infâncias na escola: agenda de acolhimento em contextos de vulnerabilidade social - Costa, Analéia Maraschin da (2023)
This dissertation study is linked to the Professional Master's Course, of the Graduate Program in Public Policies and Educational Management, Research Line LP2 Pedagogical Management and Educational Contexts. It addresses the issue of childhood visibility and School Management in Contexts of Social Vulnerability. Its general objective was to build a welcoming collaboratively agenda, for childhoods in contexts of social vulnerability, promoting more inclusive processes in the school context. For its specific objectives the dissertation prioritized: recognizing the challenges of school work with children in social vulnerability; knowing the aspects that make childhoods vulnerable in communities in situations of social vulnerability; identifying the welcoming dimensions already carried out by the school. As a theoretical framework, it included the studies by Arroyo (2012), Paro (2016), Freire (1996), Gallo (2002), Jacomini (2009) and Engestron (2013), among others. Based on research with a qualitative approach and on the Laboratory of Change, the study had as its context the São João Batista Municipal Elementary School, with its management, teachers, interns, and school employees. Developed sessions were planned in order to promote the expansive learning of the research participants, envisioning the elaboration and transformation of the object of the shared activity: the SJB's childhood embracement. Thus, the mapping and analysis actions made it possible to identify school work with children in social vulnerability challenges the precariousness of teaching working conditions, the social decline of the community, literacy in contexts of social vulnerability, and meaningful learning. As aspects that make childhood vulnerable, we observed adultization/child labor; contact with crime/violence in the territory; basic needs neglected. This process has highlighted that childhoods visibility affects the vulnerability of teaching since teachers often do not have the training conditions and even the psychological conditions to deal with the demands that emerge from this process. Considering this, the construction of welcoming agendas in schools that serve communities in vulnerable situations needs to be thought and continuously developed. From the expansive learning actions that promote the creation of a new model, we identified as germ cells the teachers' recognition of the welcoming practices already developed, as well as the indication of dimensions to compose the School's welcoming agenda. In this sense, the technical/educational product presented characterizes as a Welcoming Agenda, which is an institutional policy, particular, authorial and brings its aptness of doing a certain daily life, which welcomes a specific community by operating transformative actions, which brings at least four pillars identified in this research: listening, public policies, community, and learning.